Afghanistan ancien carrefour entre l'est et l'ouest ; actes du colloque international [...] au Musée archéologique Henri-Prades-Lattes du 5 au 7 mai 2003 (Indicopleustoi, 2005)
Contains 27 papers on Afghanistan's history from the Bronze Age to Islamic times, written by scholars and experts on history, art, epigraphy and numismatic.